New records of the Brazilian Anthomyiidae (Diptera) and a checklist of species from Palmas Grasslands Wildlife Refuge - Roberto Pereira Gomes; João Manuel Fogaça; Mariza Bortolanza; Adriana Couto Pereira (Check List, 2019)
The Anthomyiidae (Insecta, Diptera) include 1,941 species in 53 genera that are found in a wide range of habitats (forests, cities, agricultural fields). Herein, the anthomyiid fauna of the Atlantic Forest of Palmas (south of the state of Paraná) was surveyed using Malaise traps at altitudes higher than 1,000 meters. The collection of these flies was conducted in Palmas Grasslands Wildlife Refuge (PGWR) that is a full protection conservation unit (CU) surrounded by degraded areas and with high levels of endemism. A total of 12 species of anthomyiid flies (42.3% of Brazilian species) and 7 genera (58.3% of Brazilian genera) were identified, including 9 new records to Paraná (Anthomyia plurinervis (Albuquerque, 1958), A. xanthopyga (Albuquerque, 1959), Calythea comis (Stein, 1911), Coenosopsia ferrari Nihei & de Carvalho, 2004, Emmesomyia auricollis (Stein, 1918), E. sobria (Albuquerque & Couri, 1981), Leucophora maculipennis (Albuquerque, 1953), Pegomya bruchi (Shannon & Del Pont, 1926) and P. poeciloptera Malloch, 1921). Also, we examined some specimens deposited in the Department of Zoology, Universidade Federal do Paraná, the Museu Nacional, Universidade Federal do Rio de Janeiro, and the Museu de Zoologia da Universidade de São Paulo in order to update species’ distribution, leading to a new record for Rio Grande do Sul (Pegomya poeciloptera Malloch, 1921) and 3 new records for Santa Catarina (Anthomyia pluripunctata (Albuquerque, 1959), Calythea comis (Stein, 1911), Leucophora maculipennis (Albuquerque, 1953)). A key to the local genera and diagnoses of species are provided.